Effects of Therapeutic Calf Massage on Cardiac Autonomic Function in Healthy Volunteers—a Pilot Study - Siva Kumar, A. V.; Krishna Sri Lahari, A; K. N, Maruthy; Sk, Kareem; K, Maheshkumar (International Journal of Therapeutic Massage & Bodywork, 2023)
Background: Calf massage is a therapeutic intervention that improves circulation and relieves us from pain & tightness. The calf massage also improves autonomic performance by modulating the vagal tone of the cardiovascular system. Therefore, the current study was intended to determine therapeutic calf massage on cardio autonomic activity in healthy subjects. Objective: To assess the immediate effect of a single 20-min session of calf massage on cardiac autonomic modulation through heart rate variability (HRV) measurement. Materials & Methods: In this study, 26 apparent healthy female participants aged between 18 and 25 years participated. Massage over the calf muscles on both legs for 20 min was performed, and resting cardiovascular parameters and HRV parameters were measured at baseline, immediately after the massage, and during the recovery periods (10 and 30 min after the massage). Data were analyzed using one-way ANOVA followed with post hoc analysis. Results: Immediately after the massage intervention, heart rate (HR), systolic (SBP), and diastolic (DBP) blood pressure were decreased (p < .01), and the reduction was persisted at 10 min and 30 min of the recovery period (p < .01). In HRV parameters, the root mean square of successive differences (RMSSD) and high-frequency normalized unit (HF n.u.) increased, and low frequency (LF n.u.) decreased after the massage, and at the 10 and 30 min of the recovery period. Conclusion: The present study reports suggest a significant reduction in heart rate and blood pressure after the massage therapy. A drop in sympathetic tone and raise in parasympathetic tone can also attribute to the therapeutic effect.